TanDEM-X Acquisition Planning and DEM Performance in the Third Year of Operation - Schulze, Daniel; Bachmann, Markus; Borla-Tridon, Daniela; Zink, Manfred; Krieger, Gerhard (2013)
TanDEM-X is a spaceborne SAR mission with the goal to derive a global Digital Elevation Model (DEM). The two incorporated satellites fly in a close formation with distances of around 500 m. These small baselines form a single pass bistatic interferometer for accurate DEM acquisitions. The final DEM product will enter a new level of detail and accuracy on a global scale. The absolute height error shall be less than 10 m in a 90% confidence interval at a pixel spacing of 12 m. The vertical height specification for the TanDEM-X mission foresees a 90% point-to-point error of 2 m (4 m) for areas with predominant terrain slopes smaller than 20% (greater than 20%) for a 1° by 1° cell. This presentation gives an overview about the planning and the actual status of the global DEM acquisition. This includes the acquisition plan after the first two years of operation, i. e. two global coverages, including the acquisitions of the Antarctica and difficult terrain. Also, the actual performance status in terms of absolute and relative height error and the narrow relation between the DEM acquisition planning and the performance evaluation is presented.